Desalination of reverse osmosis effluent using integrated solar pond with solar still system - Al-Musawi, Osamah Abdulhameed Kadhim (2016)
A hybrid system of mini solar pond combined with single-slope still was used to increase the production of the distilled water from R.O rejections and to harness the generated thermal energy from this mini solar pond. This study is focused on the solar distillation coupled with solar pond technique as a renewable energy method in Iraq and as a case study for desalination of R.O rejects with no negative ecological effects. This eco-friendly system has a potential to maintain in the reduction of the fossil fuel energy consumptions, water supply by reusing RO effluents and maintenance of the up-stream environmental water sources. The solar pond and solar still were manufactured from steel and isolated by glass-wool with a set of isolation piping to conserve the amount of the heat captured. The meteorological data was collected (near to Baghdad) and system was observed during the period of study (50 days). Daily efficiency and recovered water were studied for 12 working hours per day, and the optimum value of mass flux was 12 kg/m2.day of the R.O. effluent. The experiment and theoretical calculations were carried during 50 days in May, June, and July 2015. Climatic conditions during the experiment were mentioned and collected throughout the period of study. Experimental tests showed the temperature profiles of the mini solar pond and the maximum temperature was 64 C at the LCZ of the mini solar pond with an efficiency of ~10.8 %. The productivity of distilled water obtained from the solar still alone, solar still integrated with mini solar pond, and sunshade added to the system was tested ~ 1.25, 2.5, and 2.77 kg/m2.day, respectively. Add to that, the efficiency of water production was evaluated ~ 24.8%, 29%, and 30.5%, respectively. The improvement percent was ranged ~ (66% - 70%) for the evaporation rate of the system.